Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Fix an odd prime $p$. Then for a positive integer $a$, I can look at the quadratic Legendre symbol Gauss sum

$$ G_p(a) = \sum_{n \,\bmod\, p} \left( \frac{n}{p} \right) e^{2 \pi i a n / p}$$

where I use $\left( \frac{\cdot}{\cdot} \right)$ to be the Legendre Symbol. We know how to calculate it explicitly, and that's all well and good.

Recently, I've had reason to consider a "prime power" Gauss Sum

$$G_{p^k}(a) = \sum_{n\,\bmod\,p^k}\left(\frac{n}{p^k}\right)e^{2\pi i a n/p^k}$$

and I've noticed that as long as $k > 1$, $G_{p^k}(a) = 0$.

A sketch of why this is true:

  1. If $k$ is even, this is very easy to see as the Legendre symbol goes away, so we are summing the $p^k$th roots of unity.
  2. If $k$ is odd, the way I see it is a bit less obvious: reduce the Legendre symbol to be $\left( \frac{n}{p} \right)$ so that it's $p$-periodic, write $n = pn' + n''$ fpr $0 \leq n' < p^{k-1}$ and $0 \leq n'' \leq p$. Reorder the sum to sum over the $p^{k-1}$ roots of unity first, which for $k > 1$ will still give $0$.

My question is this: there are many ways of viewing Gauss sums. They can be viewed as discrete Fourier transforms, generators of quadratic extensions in $\mathbb{Q(e^{2\pi i / p})}$, as eigenfunctions, natural character sums, etc. I suspect that there is some 'obvious' or 'clear' reason why these prime power Gauss sums should be zero.

Is there an obvious or clear reason why $G_{p^k}(a) = 0$?

share|cite|improve this question
I don't see any more "obvious" reason than what you gave. – i707107 Apr 17 '13 at 5:50

What follows is essentially a way of rewording the argument you gave above.

Let $\chi$ be a Dirichlet character modulo $N$, and consider the Gauss sum $$\tau(\chi)=\sum_{k=1}^{N}\chi(k)e^{2\pi ik/N}.$$ Suppose that $q|N$ is the conductor of $\chi$ so that $\chi$ is induced by a primitive character modulo $q$. Call this primitive character $\chi^{\star}.$ Then Theorem $9.10$ of Montgomery and Vaughn states that $$\tau\left(\chi\right)=\mu\left(\frac{N}{q}\right)\chi^{\star}\left(\frac{N}{q}\right)\tau\left(\chi^{\star}\right).$$ When $k\geq2$ is even, the primitive character inducing $\left(\frac{n}{p^{k}}\right)$ is $\chi_{0},$ the principle character, and so $\frac{N}{q}=p^{k}.$ This is certainly not squarefree, so the $\mu\left(\frac{N}{q}\right)$ term is zero. Similarly, when $k\geq3$ is odd, the primitive character inducing $\left(\frac{n}{p^{k}}\right)$ is $\left(\frac{n}{p}\right),$ and so $\frac{N}{q}=p^{k-1}.$ Again this not squarefree, so the $\mu\left(\frac{N}{q}\right)$ term is zero implying that for $k\geq2$ $$\sum_{n=1}^{p^{k}}\left(\frac{n}{p^{k}}\right)e^{2\pi in/p^{k}}=0.$$

share|cite|improve this answer

The value of the sum is determined by $a$ and to a lesser extent $k$. Set $e(q):= e^{2\pi \imath q}$ for any rational $q$. We consider the sum \begin{align*} G_{p^k}(a) &:= \sum_{x=0}^{p^k-1} \left(\frac x{p^k}\right) e\left(\frac {ax}{p^k}\right) = 0 + \sum_{x=1}^{p^k-1} \left(\frac xp\right)^k e\left(\frac{ax}{p^k}\right)\\ &= \sum_{\substack{x=1\\(x,p)=1}}^{p^k-1} \left(\frac xp\right)^k e\left(\frac{ax}{p^k}\right) + \sum_{\substack{x=1\\ p \mid x}}^{p^k-1} \left(\frac xp\right)^k e\left(\frac{ax}{p^k}\right)\\ &= \sum_{\substack{x=1\\(x,p)=1}}^{p^k-1} \left(\frac xp\right)^k e\left(\frac{ax}{p^k}\right) \end{align*}

where $\displaystyle \left(\frac x{p^k}\right) = \left(\frac xp\right)^k$ is a well known property of the Jacobi symbol.

We re-index by mapping $x \mapsto u+pv$ where $u$ runs from $1$ to $p-1$ and $v$ runs from $0$ to $p^{k-1} -1$. Hence, \begin{align*} \sum_{\substack{x=1\\(x,p)=1}}^{p^k-1}& \left(\frac xp\right)^k e\left(\frac{ax}{p^k}\right) = \sum_{u=1}^{p-1} \sum_{v=0}^{p^{k-1}-1} \left(\frac up\right)^k e\left(\frac{a(u+pv)}{p^k}\right)\\ &= \sum_{u=1}^{p-1} \left(\frac up\right)^k e\left(\frac{au}{p^k}\right) \sum_{v=0}^{p^{k-1}-1} e\left(\frac{av}{p^{k-1}}\right)\\ &= \sum_{u=1}^{p-1} \left(\frac up\right)^k \begin{cases} 0 &\mbox{ if } a \not\equiv 0 \mod {p^{k-1}}\\ p^{k-1} &\mbox{ if } a \equiv 0 \mod {p^{k-1}} \end{cases}\\ &= \begin{cases} 0 &\mbox{ if } a \not\equiv 0 \mod {p^{k-1}} \mbox{ or } k \mbox{ odd}\\ (p-1)p^{k-1} &\mbox{ if } a \equiv 0 \mod {p^{k-1}} \mbox{ and } k \mbox{ even} \end{cases} \end{align*}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.